A Video Tutorial for Slash Method Pattern Cracking Technique Using Richpeace CAD Application in the Flat Pattern Design Course - Puspa, Puspaneli; Novrita, Sri Zulfia; Yusmerita, Yusmerita (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
The Flat Pattern course offers instruction in the theoretical and practical aspects of creating broken patterns in accordance with design specifications. To ensure optimal learning outcomes, it is essential to provide students with updated, engaging, and practical learning media. This updated learning medium has the potential to enhance student learning outcomes and address the challenges commonly encountered in flat-pattern courses. The objective of this study is to develop a video tutorial learning medium for the slash method pattern-breaking technique using the Richpeace CAD application in a flat pattern design course. This study employs the 4D Research and Development Model method, which comprises the following four stages: The four stages of the 4D Research and Development Model method are as follows: define, design, develop, and disseminate. The alpha test stage was employed to validate this video tutorial media product with the participation of two media experts and two material content validators. The study included 35 students from the IKK FPP UNP who had previously undertaken courses in Flat Pattern Design. The data were collected through the use of validation sheets completed by media experts and an analysis of the material content, as well as through the administration of questionnaires to students regarding video tutorial media. Subsequently, the data were subjected to descriptive statistical analysis.